Azacitidine and donor lymphocyte infusions as first salvage therapy for relapse of AML or MDS after allogeneic stem cell transplantation - Schroeder, Thomas; Czibere, A.; Platzbecker, U.; Bug, G.; Uharek, L.; Luft, Thomas; Giagounidis, A.; Zohren, F.; Bruns, I.; Wolschke, C.; Rieger, K.; Fenk, R.; et al. (Leukemia, 2013)
The combination of azacitidine and donor lymphocyte infusions (DLI) as first salvage therapy for relapse after allogeneic transplantation (allo-HSCT) was studied in 30 patients with acute myeloid leukemia (AML; n=28) or myelodysplastic syndromes (MDS; n=2) within a prospective single-arm multicenter phase-II trial. Treatment schedule contained up to eight cycles azacitidine (100 mg/m2/day, days 1-5, every 28 days) followed by DLI (from 1-5 × 106 to 1-5 × 108 CD3+cells/kg) after every second azacitidine cycle. A median of three courses azacitidine (range 1-8) were administered, and 22 patients (73%) received DLI. Overall response rate was 30%, including seven complete remissions (CRs, 23%) and two partial remissions (7%). Five patients remain in CR for a median of 777 days (range 461-888). Patients with MDS or AML with myelodysplasia-related changes were more likely to respond (P=0.011), and a lower blast count (P=0.039) as well as high-risk cytogenetics (P=0.035) correlated with the likelihood to achieve CR. Incidence of acute and chronic graft-versus-host disease was 37% and 17%, respectively. Neutropenia and thrombocytopenia grade III/IV occurred during 65% and 63% of treatment cycles, while infections were the most common grade III/IV non-hematological toxicity. Azacitidine and DLI as salvage therapy is safe, induces long-term remissions and may become an alternative for patients with AML or MDS relapsing after allo-HSCT.